Halal Purchase Intention Among the Singaporean Muslim Minority - Abu-Hussin M.F.; Johari F.; Hehsan A.; Mohd Nawawi M.S.A.B. (Routledge, 2024)
Muslim consumers awareness toward halal foods and products has been increasing. The halal concept becomes consumers vital concern as it covers wide areas of consumption, though one might perceive it as only a food-related issue. Given this background, this article aims to investigate the factors that influence consumers intention to purchase halal-certified foods and products. By using Ajzens theory of planned behavior (TPB) as a theoretical framework, this research employed a quantitative survey with a sample of 332 Muslim consumers living in Singapore to examine Singaporean Muslim preferences in purchasing halal foods and products. Data gathered from the survey were then explored and analyzed. Multiple regression analysis results indicate that all TPB variables have a positive and significant influence on the intention to purchase halal-certified products among the Muslim minority in Singapore. 2017 Taylor & Francis.